1981
DOI: 10.1080/14640748108400800
|View full text |Cite
|
Sign up to set email alerts
|

One Process, Not Two, in Reading Aloud: Lexical Analogies Do the Work of Non-Lexical Rules

Abstract: It is widely held that there are two (non-semantic) processes by which oral reading may be achieved: (a) by known words visually addressing lexical storage of their complete orthography and phonology; (b) by parsing a letter string into graphemes which are translated by rule into phonemes. Irregular words (HAVE) rely on the former, new and non-words rely on the latter. Recent evidence casts doubt on this view; to meet some of this data a revised version is presented. An alternative view is that the phonology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(118 citation statements)
references
References 9 publications
5
112
1
Order By: Relevance
“…The alternative view of pronunciation is that forwarded by Glushko (1979) and subsequently advocated by Kay and Marcel (1981). The basic idea of Glushko's "activation and synthesis" model is best explained in his own words:…”
Section: Discussionmentioning
confidence: 99%
“…The alternative view of pronunciation is that forwarded by Glushko (1979) and subsequently advocated by Kay and Marcel (1981). The basic idea of Glushko's "activation and synthesis" model is best explained in his own words:…”
Section: Discussionmentioning
confidence: 99%
“…Most models of word reading (e.g., Buchanan & Besner, 1993;Carr & Pollatsek, 1985;Coltheart, 1978Coltheart, , 1985Coltheart et al, 1993;Morton & Patterson, 1980;Paap & Noel, 1991;Patterson & Morton, 1985;Reggia, Marsland, & Berndt, 1988;Seidenberg & McClelland, 1989;Shallice & McCarthy, 1985, but see Kay & Marcel, 1981;Van Orden, Pennington, & Stone, 1990, for exceptions) have (at least) two ways of pronouncing written words-that is, of mapping orthography to phonology. The first derives the meaning (semantics) of the word as an intermediate representation; the second bypasses semantics and maps directly from orthography to phonology.…”
Section: Cognitive Remediation Of Acquired Dyslexiamentioning
confidence: 99%
“…Marcel (1980) suggested that in the process of reading, the reader parses the letter string not only by a cumulative exhaustive procedure, but also according to morphemic specifications that are in the visual lexicon. Kay and Marcel (1981) presented subjects with nonwords containing legal morphemes and demonstrated that naming latencies depended on the pronunciation regularity of the morphemes. Kay and Marcel therefore suggested that morphemic units are probably the basis on which beginning readers generate phonology.…”
Section: Methodsmentioning
confidence: 99%